Comparison of ropivacaine alone or with dexamethasone as an adjuvant for reducing pain during positioning for neuraxial blockade with ultrasound-guided fascia iliaca compartment block - Dubey, Suvir; Ambi, Uday; Taank, Priya; Singh, Shalendra; Marwah, Vikas (International Journal of Research in Medical Sciences, 2020)
Background: Comparison of ropivacaine alone or with dexamethasone as an adjuvant for reducing pain during positioning for neuraxial blockade with ultrasound-guided fascia iliaca compartment block. Methods: In this double-blinded study, a total of 60 patients between 18 to 80 years of age, undergoing surgery for hip fracture were enrolled. Patients in Group A received 40 ml of 0.25% ropivacaine +2 ml saline and patients in Group B received 40 ml of 0.25% ropivacaine +8 mg dexamethasone. USG guided FICB and postoperative monitoring was done by the chief investigator who was unaware of group allotted and drug administered. Results: There is no significant difference in the heart rate between the two groups after 30 min of the block. The variation of systolic blood pressure of both the group for the first 30 min after giving FICB block was not significant (p>0.05). The absolute value of diastolic blood pressure (DBP) was significantly lower in Group B compared to group A just before the block, a variation of DBP with time was not significant. There was a gradual improvement of pain score from mean 6.7 in Group A and 6.6 in Group B at 0 min to score of 2 at the end of 30 min in both the group. This improvement was achieved earlier in Group B compared to Group A, although the difference was not significant (p>0.05). Vital parameters like HR, SBP, DBP, SpO2 values were similar in both the groups. No patients in either group required any interventions both pre-operatively and pos-operatively. Time of rescue analgesia was noted with the VAS score was significantly more in Group B (p≤0.004). The incidence of hematoma, accidental intravascular injection, convulsion, and paresthesia were nil in both groups. Conclusions: Although both the groups had comfortable and pain-free positioning for administering spinal anaesthesia before surgery. USG guided FICB is easy to perform block and give excellent analgesia for positioning and mobilization of hip fracture patients pre and post-operatively both, and dexamethasone as an adjuvant to 0.25%ropivavaine prolong its local anesthetic effect significantly.